Could anaesthesia be a key factor for the good outcome of bone ablation procedures? A retrospective analysis of a musculoskeletal interventional centre - Arrigoni, Francesco (Br J Radiol, 2021)
OBJECTIVE: To choose the best anaesthetic approach through the retrospective review of different bone ablation procedures. METHODS AND MATERIALS: We retrospectively evaluated 118 ablation procedures carried out in our institute over the last 30 months. Three different anaesthetic approaches were used: general anaesthesia, i.v. sedation/analgesia and loco-regional anaesthesia (brachial plexus block, spinal anaesthesia). The outcomes were evaluated based on three parameters: technical success, patient comfort (Scale 1–5) and operator comfort (Scale 1–5). RESULTS: The 118 interventional procedures were carried out on 62 benign and 56 malignant bone lesions. The overall procedural success rate was 100%. Three cases were treated under general anaesthesia: patient comfort was 5/5 in all cases; operator comfort was 5/5 in one case, and 4/5 in two cases. Twenty-one patients underwent sedation/analgesia: in three patients with benign bone lesions, patient comfort was 1/5 and operator comfort 3/5; in two patients with malignant bone lesions, patient comfort was 3/5 and operator comfort 4/5. Ninety-four patients underwent loco-regional anaesthesia: patient and operator comfort was 5/5 in all cases. CONCLUSION: Based on our experience, loco-regional anaesthesia is probably the best anaesthetic approach during bone ablation procedures. Benign bone lesions ablation are the more painful procedures. ADVANCES IN KNOWLEDGE: This is the first paper that systematically investigates about the best anaesthesiological support for IR procedures.